Secure Data Hiding Using Neural Network and Genetic Algorithm in Image Steganography - Sakshi; Kaur, A (International Journal of Computer Sciences and Engineering, 2025)
Due to the high growth of Internet and its applications over the network, there is a need of high level of security whilw doing the data to transfer between the networks. Steganography is a technique of hiding the data over the medium so that no one knows that there is any communication going on except the sender and receiver. This paper gives an approach for Image Steganography to improve the level of security for information exchange over the web. The 24-bit RGB image is picked as a cover picture which hides the encrypted secret message inside red, green and blue pixel values. The combination approach of DWT, Masking, Artificial Neural Network (ANN) and Genetic Algorithm (GA) has been implemented on cover image and text data that is to be hidden in cover image is encrypted with Elgamal and AES algorithm (hybrid approach). This technique gives a level of security to the mystery message which makes it troublesome for the gatecrashers to remove the concealed data. A Peak Signal-to-Noise Ratio, Mean Square Error and Decryption Time is calculated which measures the quality of images used. Larger PSNR and lower MSE value indicates lower distortion and hence a better quality of image.